ANALISIS PERAN KOMUNIKASI DALAM MENINGKATKAN KINERJA PENGURUS UKM BAND UNIVERSITAS ESA UNGGUL TANGERANG - Jessica Angelina Simanjuntak; Darren Richie Setiawan (Cahaya Ilmu Bangsa, 2025)
Communication is the key to running an organization. Organizational communication regulates the relationships that exist within the organization both in groups and individuals, becomes a reference in problem solving, and to support the interests of interaction with all parties. The purpose of this research is to find out how influential the communication of the head of the organization is in motivating the members of the management of UKM Band, Esa Unggul University, Tangerang Campus. The research method used is descriptive qualitative research method where data is obtained directly through observation as a participant and through indirect short interviews on Google Form. The results of the research analysis show that the Head of UKM Band applies a participative leadership style, which is reflected in two main communication approaches. They are The Relinquishing Style and The Equalitarian Style. The final result of this research explains that a leader's communication pattern has a very relevant impact on the performance of organizational members. The leader's ability to accept criticism and suggestions, provide opportunities for discussion or argument in decision making, and show empathy to members are key components in building a comfortable and motivating organizational atmosphere.